How can we know the existence of God: Anselm and Aquinas? - Chibuikem C. Nnaeme (Verbum et Ecclesia, 2015)
This article is concerned with how we can know about the existence of God. In attempting to do this, the article will single out two medieval thinkers, Anselm and Aquinas, and will examine their stances on the subject. The former holds, as exemplified in his ontological proof,that human beings can rationally know the existence of God, whilst the latter objects to theformers claim by proffering that human beings can know Gods existence through effects of Gods creation. Over the years these positions have appealed to people who defend eitherstr and of the argument. Such a followership makes worthwhile my efforts to contribute to the ongoing debate. It is my intention to show the argument of each of these positions and indicate which is more plausible to human beings. It is vital to note that Anselm and Aquinas both accept the existence of God; therefore, the existence of God is not in question for them.The article will only concentrate on where the two thinkers differ in terms of how human beings can know Gods existence. Intradisciplinary and/or interdisciplinary implications: This article challenges idealistsphilosophy that human beings can prove Gods existence from the concept, God, as epitomisedby Anselms ontological argument. The critique of the argument through the application of Aquinass realism exposes the limitedness of the human beings in epistemological conception of the absolute metaphysical reality.